Hydrogen/deuterium adsorption and absorption properties on and in palladium using a combined plane wave and localized basis set method. Issue 16 (29th May 2020) - Sakagami, Hiroki; Tachikawa, Masanori; Ishimoto, Takayoshi
Abstract: Detailed information on the H/D isotope effects for adsorption on the surface and absorption in the bulk is important for understanding the nuclear quantum effect. To achieve this, we developed a new theoretical approach, namely, the combined plane wave and localized basis set (CPLB) method. By using the multicomponent quantum chemical method, which takes into account the quantum effect of a proton or deuteron, with the localized part of the CPLB method, direct analysis of the H/D isotope effect about adsorption and absorption is carried out. In this study, we performed a theoretical investigation of the H/D isotope effects for adsorption on a Pd(111) surface and absorption in bulk Pd. We clearly showed an H/D isotope effect on geometry during adsorption and absorption. Our developed CPLB approach is a powerful tool for analyzing the quantum nature of H/D in surface, bulk, and inhomogeneous systems. Abstract : It is important to understand the geometrical and energetic H/D isotope effect due to the nuclear quantum effect in metal‐hydrogen interactions, such as adsorption and absorption. To achieve this, a new theoretical approach, namely, the combined plane wave and localized basis set (CPLB) method, was developed and applied to the Pd‐H systems. We clearly demonstrated that the CPLB method is a powerful tool for analyzing the H/D quantum effect in surface and bulk metal.